GENDER ANALYSIS ON TALK DOMINANCE IN GROUP DISCUSSION OF ENGLISH AMONG STUDENTS OF ENGLISH EDUCATION DEPARTMENT AT UIN ALAUDDIN MAKASSAR - St. Azisah; Kaharuddin; Hikma, Nurhikma Mansyur (Univeristas Islam Negeri (UIN) Alauddin Makassar, 2023)
This study aims to prove the difference in talk dominance between the male group and the female group in English Education Department batch 2019 at UIN Alauddin Makassar.Moreover, this study was conducted to know the factors that cause the occurrence of talk dominance in the English Education Department batch 2019 at UIN Alauddin Makassar. This study used a qualitative descriptive design to prove whether there is talk dominance between the male group and the female group in the English Education Department batch 2019 at UIN Alauddin Makassar,. The data were taken from classroom observations via Zoom application when the students were discussing. The data were analyzed based on the theory of Kaharuddin and Ismail (2017:146) in which there were four stages: collection, identification, classification, and explanation. To find out the factors that led to the talk dominance, the researcher made questions on Google form and distributed them to 42 students of the English Education Department batch 2019 at UIN Alauddin Makassar. The result showed that there were 88 sentences produced by the students (male and female). There were 25 sentences produced by the male group and 63 by the female group. There it can be concluded that women's groups dominated the discussion. Furthermore, the factors for the occurrence of talk dominance were; intelligence factors, learning motivation factors, learning strategy factors, learning facilities, teacher responses, and the influence of friends. Keywords: Gender Analysis, Speaking, Talk Dominance, Group Discussion